0526 User Satisfaction With New Foam Cushion Full Face Mask - Hevener, William; Blase, Amy; Valentine, Kate; Garcia, Arturo; Eardley, Jared; Benjafield, Adam (Sleep (New York, N.Y.), 2019)
Introduction Using a silicone-based full face mask (FFM) for PAP therapy can create problems for patients which may result in lower adherence. Mask discomfort, mask leak, and prolonged facial marks after use may discourage a patient from continuing with PAP therapy long term. Patients with facial hair present an additional challenge for obtaining a good mask seal with FFMs. The objective of this study was to evaluate the performance of a new mask made with a foam cushion to address common issues with FFMs. Methods Current FFM users who had been compliant on PAP therapy for at least 6 months were asked to trial the foam cushion mask [FCM] (AirTouch F20, ResMed) for at least 30 but up to 60 days. At the end of the study, participants completed a questionnaire rating seal, comfort, facial marks, and overall performance of the study mask. Additionally, PAP therapy metrics including usage, leak, pressure, and residual AHI were collected. Results Of 234 participants enrolled, 201 completed all 60 days with the FCM. For overall performance and comfort, 90.5% and 85.6% of participants respectively, rated the mask as ‘good’ or ‘very good’. The majority (84%) of participants either had no facial marks or marks that dissipated within 30 minutes of taking the mask off. The 95th percentile mask leak decreased by 3.3 L/min (from 19.6 L/min to 16.3 L/min, p=0.001) and 85.1% of participants rated seal as ‘good’ or ‘very good’. At baseline, there was a statistically significant difference in 95th percentile mask leak between men with and without facial hair (24.9 L/min vs 17.0 L/min, p=0.008); this difference disappeared with the FCM (17.6 L/min vs 15.7 L/min, p=0.490). PAP usage, pressure, and residual AHI did not change significantly during the study. Conclusion These results demonstrate the importance of mask selection for solving common issues experienced by PAP users and that this FCM is an appropriate option. A FCM may also be a good alternative for men with facial hair who have issues with obtaining a good mask seal. Support (If Any) ResMed